Data Mining Tools and Techniques for Big Data: A Review - Jatinder Verma (International Journal of Advanced Science and Technology, 2020)
Huge Data refers to monstrous arrangement of information which is unpredictable to overseen pertaining to customary submissions. These days, it incorporates gigantic, inexhaustible organized, semi-structure, and unstructured information just as shrouded information that are created and accumulated from a few fields. Problem with overseeing Big Data incorporate separating, dissecting, imagining, sharing, stockpiling, moving and looking through such information. At present, the customary information handling apparatuses also, its applications are not fit for overseeing such changed information. In this way, creating viable and productive Big Data Mining methods. This, thus, has opened doors to utilize the misusing man-made consciousness strategies for Big Data on the board. This study explores the best Big Data Mining procedures and their method of reasoning applications in different therapeutic and logical domains.